Modified differential evolution algorithms for multi-vehicle allocation and route optimization for employee transportation. Issue 7 (2nd July 2020) - Pitakaso, Rapeepan; Sethanan, Kanchana; Srijaroon, Nitikorn
ABSTRACT: This research aims to develop decision making on how to provide employees with a transportation service that is fast, cost effective and timely. This work is different from previous research in that it integrates the bus stop determination, bus assignment and the bus route design sub-problems of an employee transportation service for a large-scale company. The objective of this article is to minimize total travelling costs and the total rental costs of the heterogeneous fleet capacitated vehicles. A mathematical model is applied to solve for small-size problems. Additionally, for large-size problems, five modified differential evolution (MDE) algorithms are developed to solve the three sub-problems simultaneously. New rules used in the mutation process of the MDE algorithms and an advanced design of the encoding and decoding method are presented in this article. The results demonstrate that the MDE is an efficient transportation management system for any organization.